2013
DOI: 10.1063/1.4792160
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of polarized microwaves with planar arrays of femtosecond laser-produced plasma filaments in air

Abstract: The interaction of polarized microwaves with subwavelength arrays of parallel plasma filaments, such as those produced by the propagation of high-power femtosecond laser pulses in ambient air, was investigated by calculating the reflection and transmission coefficients as a function of the incidence angles using the finite-difference time-domain (FDTD) method. The time evolution of these coefficients was calculated and compared with experiments. It is found that the plasma filaments array becomes transparent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Characterizing the geometry of filaments, and the distribution of free electrons therein, during the process of VHMM formation, along with quantitative analysis of the influence of structural inhomogeneity on the performance of VHMMs, are the foci of our current work, and are planned to be published in further articles. Finally, we note that while recently the first studies of the interactions of microwave radiation with the arrays of filaments have been reported by Merian et al [38], further studies including pulsed microwave radiation interactions with filaments are necessary. In this work, we have considered several different applications of VHMM structures for microwave signal manipulation.…”
mentioning
confidence: 97%
“…Characterizing the geometry of filaments, and the distribution of free electrons therein, during the process of VHMM formation, along with quantitative analysis of the influence of structural inhomogeneity on the performance of VHMMs, are the foci of our current work, and are planned to be published in further articles. Finally, we note that while recently the first studies of the interactions of microwave radiation with the arrays of filaments have been reported by Merian et al [38], further studies including pulsed microwave radiation interactions with filaments are necessary. In this work, we have considered several different applications of VHMM structures for microwave signal manipulation.…”
mentioning
confidence: 97%
“…Propagation over such long distances is a result of the dynamic balance between the focusing Kerr nonlinearity, diffraction, and plasma defocusing due to multiphoton absorption. A proper arrangement of plasma channels into arrays built of multiple filaments can lead to control and efficient guiding of electromagnetic radiation in air . Dielectric and hollow-core metallic waveguide configurations , were predicted theoretically and demonstrated experimentally to guide microwave radiation.…”
mentioning
confidence: 99%
“…Although this approach offers a way to counteract the diffraction of a radar signal over some distance, the issues of beam steering and coupling microwave signals into such waveguides are likely to be challenging. Finally, very recently, Marian et al 6 reported parametric studies of interactions of microwaves with subwavelength arrays of parallel plasma filaments. Although these studies elucidated reflection and transmission properties of various periodically and randomly arranged filament arrays, no specific physical mechanism enabling guiding, focusing or steering of the microwave beam was discussed.…”
mentioning
confidence: 99%